If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6z + -30 = 0 Reorder the terms: -30 + 6z = 0 Solving -30 + 6z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 6z = 0 + 30 Combine like terms: -30 + 30 = 0 0 + 6z = 0 + 30 6z = 0 + 30 Combine like terms: 0 + 30 = 30 6z = 30 Divide each side by '6'. z = 5 Simplifying z = 5
| x^6+3x^5-18x^4=0 | | 14x+7=5x-6x | | x-0.25x=24.00 | | -8=8+4u | | -18=4v-6v | | 3x=y(x+y+19) | | 5(v-9)-1=-7(3v+7)-v | | 11=3(v-3)-7v | | (A+6)+((A+2)+6)=(3A)+6 | | -13=3x-7 | | 2.1x+45.2+3.2-8.4x= | | 6x+12y=20 | | 14x*7=5x-6x | | -8x+4(x+6)=20 | | 5(4n-8)=-28+8n | | -3(r+4)=-41 | | k+4-7=3 | | 2.1x+45.2+3.2-824x= | | -16w+7.38=-16.7w+2.97 | | 7y+49=9(y+7) | | 7r-6r=5 | | 20=10v-5v | | 6=-6u+4(u+4) | | 6m-2=32 | | 0.3x=0.09 | | 6(x+3)=3(8+4x)-6 | | 20-14s=-20-19s | | 2-15-5=12 | | 4(x-3)+5=53 | | 4(2w-3)=2(3w+5) | | t^3+6t^2=25t+150 | | 3(X-2)=Xm+7 |